BEGINNING OF POLITICAL ACTIVITY OF EUMENES OF CARDIA - V. Mikhaylov (Гуманитарные и юридические исследования)
The article examines the beginning of the political career of one of the closest Macedonian kings Philip II and Alexander III, and later a participant in the famous wars of the Diadochi - Eumenes of Cardia. The history of the early Hellenistic period, in particular the biographies of the leaders of that era, continues to arouse interest among researchers. Foreign literature is replenished with new monographs dedicated to outstanding representatives of the period that followed the death of Alexander. In our opinion, the personality of Eumenes of Cardia is unfairly ignored in Russian historiography. The relevance of the work lies in the need to highlight the first years of the life of the above-mentioned political and later military leader. The article attempts to clarify the origin of Eumenes from Cardia, his formation and the duties he performed at the Macedonian court during the time of Philip II, as well as his service during the Asian campaign of Alexander the Great. In addition, in the context of research and analysis of the biography of Eumenes of Cardia, his administrative position of the royal «secretary» in the Macedonian kingdom is considered. Being in this post entailed the fulfillment of such duties as keeping the royal personal diary, which speaks of the important status of the person engaged in this activity. In this vein, we should consider the problem of «ephemeris» and «hypomnematics» - everyday recordings and planned projects, respectively, thanks to which we know about the last days of Alexander the Great's life and which Eumenes of Cardia supposedly recorded as the «аrchigrammatheus» of the king.